Let E =|-3|*|3|*|-4|+|-7|-|3|-|-2

First thing, we need to rewrite the absolute values in the form of a real number.

Let us simplify.

l-3 l = 3

l3l = 3

l-4l = 4

l -7 l = 7

l-3l = 3

l-2l = 2

Now we will rewrite the numbers.

==> E = 3*3*4 + 7 -3 -2

Now the priority in the operation is to the multiplication.

So we first multiply 3*3*4 = 36

==> E = 36 +7 - 3 -2

Now we will add and subtract at the same time.

7-3-2 = 2

==> E = 36 + 2 = 38

**Then the answer is 38.**

|-3|*|3|*|-4|+|-7|-|3|-|-2|

((3 x 3) x 4) + (7 - 3 -2)

(9 x 4 )+ 2

36 + 2

38

We'll apply the rule of absolute value:

|a| = a, for a>0

|a| = - a, for a<0

|a| = 0, for a = 0

Comparing, we'll get:

|-3| = -(-3) = 3, because -3<0

|3| = 3, because 3 > 0

|-4| = -(-4) = 4, because -4<0

|-7| = -(-7) = 7, because -7<0

|-2| = -(-2) = 2, because -2<0

Now, we'll substitute the results:

|-3|*|3|*|-4|+|-7|-|3|-|-2| = 3*3*4 + 7 - 3 - 2

We'll multiply first:

36 + 2 = 38